The Landscape of Drug-Resistant Tuberculosis in South-East Asia (SEA) Region: A Burden of Disease and Challenges in Detection - Ahmed, Akash; Khan, Nabila; Ferdous, Shehreen; Nayara Noor E Fatima; Khan, Afroza; Mouly, Tonima Fairooz; Sultana, Sadia (Bangladesh Journal of Microbiology, 2025)
Tuberculosis, mainly caused by Mycobacterium tuberculosis, is a serious bacterial infection that primarily infects the respiratory system but can spread to other organs of the body. Approximately one-third of the world’s population is infected with MTB, affecting people from all age groups. Out of the 30 high TB burden countries, 6 of them are in South-East Asia (SEA) region accounting for 44% of the global TB burden. This review looks at the distribution of TB cases within the SEA region. It further explores some of the underlying causes of drug-resistant TB throughout history and how human activities has led to its proliferation. Different phenotypic and molecular methods in diagnosing drugresistant TB are also discussed in this review. Comparative analysis between the different methods have also been made in this review. In order to eradicate TB, emphasis must be put on efficient diagnostic techniques, preventative measures and adequate treatment. Bangla. J. Microbiol. 2025, Vol. 41, P: 1-8